2014
DOI: 10.4028/www.scientific.net/msf.778-780.607
|View full text |Cite
|
Sign up to set email alerts
|

4H-SiC MOS Capacitors and MOSFET Fabrication with Gate Oxidation at 1400°C

Abstract: This paper compares the performance of 4H-SiC MOS capacitors and MOSFETs made using the conventional NO annealing process and a high-temperature (1400°C) dry oxidation process. Through extensive C-V, G-ω, I-V and Hall measurements, the limitations of both the processes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The broadening of the G p / ω curve can be correlated with the surface potential fluctuations. The surface potential fluctuation ( η ) determined in our calculation are in good agreements with those reported by Naik and Chow in similar MOS capacitors . These surface fluctuations can be associated to the fluctuation on the lateral homogeneity of donors concentration in nitridated SiO 2 /4H‐SiC interfaces .…”
Section: Resultssupporting
confidence: 89%
“…The broadening of the G p / ω curve can be correlated with the surface potential fluctuations. The surface potential fluctuation ( η ) determined in our calculation are in good agreements with those reported by Naik and Chow in similar MOS capacitors . These surface fluctuations can be associated to the fluctuation on the lateral homogeneity of donors concentration in nitridated SiO 2 /4H‐SiC interfaces .…”
Section: Resultssupporting
confidence: 89%
“…[6][7][8][9][10] Recent reports on high-temperature oxidation of 4H-SiC have shown that this process could be beneficial for the 4H-SiC/SiO 2 interface. [11][12][13][14] It has been reported 12 that as-grown 4H-SiC oxidized at 1500°C resulted in a 4H-SiC MOSFET with maximum field-effect mobility of 40 cm 2 /V s; here we investigate a similar effect for the 3C-SiC/SiO 2 interface. In this study, the highest temperature used for oxidation of 3C-SiC was 1400°C, because of the limit imposed by the melting point of Si (1414°C).…”
Section: Introductionmentioning
confidence: 69%
“…4(a) shows the normalized parallel conductance (G p /ω) data for the sample oxidized at 1300 ℃. [11,12,14]. It is considered that the higher oxidation temperature can effectively reduce the accumulation of residual byproduct at the SiO 2 /SiC interface.…”
Section: Density Of Interface Statesmentioning
confidence: 99%
“…The work reported by Kikuchi et al showed a very low D it in a 14 nm oxide thickness sample by thermal oxidation at 1300 ℃ with O 2 annealing, in which the temperature window for the ideal reaction of SiC thermal oxidation in O 2 ambience with a standard atmospheric pressure was approximately estimated to be 1100~1400 ℃ [10,11]. Recently, higher oxidation temperature up to 1400 ℃ was also used to form the SiO 2 reported by Naik et al [12], however the results processed in 1400 ℃ were not as good as the expectation of better mobility at such higher oxidation temperature, and a channel mobility of corresponding MOSFETs was only 2 cm 2 /Vs. In this case, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation